Perception regarding the NICE guideline on antibiotic prophylaxis against infective endocarditis following dental procedures: a cross-sectional study - Mohd Yunus, Siti Salmiah; Syed Nabil; Rashdi, Muhd Fazlynizam; Nazimi, Abd Jabar; Nordin, Rifqah; Tan, Huann Lan; Maskon, Oteh; Che Hassan, Hamat H.; Khaithir, Tzar Mohd Nizam; Abdul Aziz, Aznida Firzah; Ng, Yee Guan; Ismail, Ridwan Yeop; et al. (Multidisciplinary Digital Publishing Institute, 2023)
This study explores the opinions of Malaysian clinical specialists on the antibiotic prophylaxis against infective endocarditis (IE) as described in the 2008 National Institute for Health and Care Excellence (NICE) guideline. This cross-sectional study was performed from September 2017 to March 2019. The self-administered questionnaire comprised two sections: background information of the specialists and their opinions on the NICE guideline. The questionnaire was distributed to 794 potential participants, and 277 responded (response rate of 34.9%). In general, 49.8% of the respondents believed that clinicians should adhere to the guideline, although the majority of oral and maxillofacial surgeons (54.5%) actually disagreed with this view. The dental procedures that were perceived as presented moderate-to-high risk for IE were minor surgery for an impacted tooth with a recent episode of infection, dental implant surgery, periodontal surgery and dental extraction in patients with poor oral hygiene. The cardiac conditions that were strongly recommended for antibiotic prophylaxis were severe mitral valve stenosis or regurgitation and previous IE. Less than half of Malaysian clinical specialists agreed with the changes in the 2008 NICE guideline, contributing to their insistence that antibiotic prophylaxis is still needed for high-risk cardiac conditions and selected invasive dental procedures.